2010
DOI: 10.5735/086.047.0501
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the Finnish Agri-Environment Scheme are Needed in Order to Support Rich Farmland Avifauna

Abstract: This tutorial demostrates the use of ordination methods in R package vegan. The tutorial assumes familiarity both with R and with community ordination. Package vegan supports all basic ordination methods, including non-metric multidimensional scaling. The constrained ordination methods include constrained analysis of proximities, redundancy analysis and constrained correspondence analysis. Package vegan also has support functions for fitting environmental variables and for ordination graphics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…Previous research has indicated that specialist, conservation priority farmland birds respond differently to variation in landscape variables to more generalist species in the same assemblages (Concepción and Díaz 2010, Filippi‐Codaccioni et al 2010, but see Vepsäläinen et al 2010). It is noteworthy, however, that the subset of specialists considered here did not show clear differences from the results for the full set of species.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has indicated that specialist, conservation priority farmland birds respond differently to variation in landscape variables to more generalist species in the same assemblages (Concepción and Díaz 2010, Filippi‐Codaccioni et al 2010, but see Vepsäläinen et al 2010). It is noteworthy, however, that the subset of specialists considered here did not show clear differences from the results for the full set of species.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of a national causal relationship, this could reflect avoidance of the more marginal, mixed farming areas where spring cereals are more common by birds found typically on predominantly arable farmland, where spring cereals are rare (Siriwardena et al 2000). Conversely, farmland heterogeneity tended to have positive effects (Table 5c): heterogeneity in cropping is also often a positive influence on farmland bird presence or abundance (Schläpfer 1988, Benton et al 2003, Sheldon et al 2004, Vepsäläinen et al 2010), and will usually be increased, in practice, by adding (spring) break crops to simple cereal‐based crop rotations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations